2013
DOI: 10.5301/hipint.5000023
|View full text |Cite
|
Sign up to set email alerts
|

Primary Stability of a PGLA/Polydioxanone Membrane for Potential Autologous Chondrocyte Implantation in the Hip Joint. a Cadaveric Study

Abstract: The purpose of this cadaveric study was to evaluate the primary stability of a membrane 
(resorbable polyglactin-910/poly-p-dioxanone) for autologous chondrocyte implantation (ACI) inserted by press-fit into defects in the femoral head and acetabulum. The stability of the membrane was evaluated after implantation in a cartilage defect on both sides of the joint in 12 hips in six cadavers. The hip was manually put through a full range of motion for 50 cycles after each lesion had been created and filled, starti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Remove the fixation solution, and wash cells with 1× PBS (pH adjusted to 4.2) 1-2 times (3). Add a filtered 2% Alizarin Red solution to the fixed cells and incubate them at 37°C for 10-20 minutes (Note: monitor staining under a microscope every 2-5 min) (4). Remove the Alizarin Red solution, and rinse cells with PBS 1-2 times (5).…”
Section: Osteogenic Induction Of Hbascsmentioning
confidence: 99%
See 3 more Smart Citations
“…Remove the fixation solution, and wash cells with 1× PBS (pH adjusted to 4.2) 1-2 times (3). Add a filtered 2% Alizarin Red solution to the fixed cells and incubate them at 37°C for 10-20 minutes (Note: monitor staining under a microscope every 2-5 min) (4). Remove the Alizarin Red solution, and rinse cells with PBS 1-2 times (5).…”
Section: Osteogenic Induction Of Hbascsmentioning
confidence: 99%
“…Place in absolute propylene glycol for 5 minutes to avoid transferring water into the Oil Red O. (3) Stain in Oil Red O solution for 8 minutes in 60°C oven (4). Rinse in 85% propylene glycol solution for 5 minutes (5).…”
Section: Adipogenic Induction Of Hbascsmentioning
confidence: 99%
See 2 more Smart Citations
“…The closest approximation to the natural environment is offered by the human cadaveric hip, which could be used to simulate the gait cycle in the post-operative rehabilitation period 10,12 . Previous studies testing cartilage repair in a cadaveric model have used simple sinus cyclic loading in both the knee and hip joint 19,21,36 . Fontana et al have recently reported on the stability of polydioxanone scaffolds in a cadaveric hip joint using continues passive motion performed by a manual operator 36 .…”
Section: Discussionmentioning
confidence: 99%